Sex differences in utilizing effective mass among taekwon-do athletes performing turning and side kick - Góra, T.; Mosler, D.; Ortenburger, D.; Wasik, J. (Physical Activity Review, 2024)
Introduction: The gender type of fighters and the technique of movement may have a significant impact on the level of effectiveness of sporting rivalry, yet their significance may differ depending on a multitude of factors. Hence, the aim of this research was to evaluate the impact of the effective mass and foot acceleration on the force of the turning kick and the side kick depending on the gender type of competitors represented.